Determination of the TOE Factors influencing the Adoption of Internet Banking Services on SMEs in Yemen: A Moderated Mediation Approach - Nabil, Al-Fahim; Abdulghafor, Rawad Abdulkhaleq Abdulmolla (Springer Nature Singapore Pte Ltd., 2021)
The main purpose for carrying out research on the adoption of the internet banking services is due to the lack of empirical studies on Yemeni internet banking services. The objective of this study is to explore and investigate the factors of Technology-Organization-Environment theory (TOE) that play a main role in the implementing of Internet banking services by SMEs in Yemen. Four exogenous variables, one mediator, one moderator, and one endogenous variable make up the current study's framework. The exogenous variables consist of security, relative advantages, government support, top management and organization readiness as mediator as well as organization type is moderator while the endogenous variables comprise of intention towards Internet Banking (IB) for banks customers (SMEs). This research also identifies the role of organization readiness as mediating variable that impact SMEs’ intention to adopt Internet banking service and also the role of organization type as a moderator between organization readiness and Internet banking adoption. The current study's sample included 314 people who were analyzed using Partial Least Square PLS-SEM to look for causal links between the study's latent variables. The findings showed that security, relative advantages, government support, top management and organization readiness have a significance and positive effect on intention towards Internet banking adoption among SMEs in Yemen. Furthermore, the findings of the study reveal that organization readiness has a mediating influence on the relationship between TOE factors and intention towards IB adoption among SMEs. Moreover, the results indicate organization type moderates the relationship between organization readiness and intention to adopt IB. In conclusion, the finding shows that SMEs businesses are able to operate more effectively by implementing a broad set of IB products through automating many of their major banking activities and through electronic communication with their banks.